Security of Internet of Things edge devices. (10th February 2020) - Lv, Zhihan
Summary: The purpose of the study is to meet the more needs of the future social development for the Internet of things (IoT) and make IoT better provide more convenience for people and reduce the risk of data leakage in the IoT system. Starting with the IoT edge devices, the centralized and distributed hit rate and average corresponding speed of the edge nodes are studied. Meanwhile, the gateway security of the edge devices designed is discussed to obtain a more reliable gateway. The research results show that the Max‐PSN cache algorithm proposed in this article is superior to the other two algorithms in terms of hit rate and average response speed of centralized and distributed fog systems, which shows the effectiveness of the cache algorithm. The gateway designed shows good randomness through frequency detection and poker detection, which can effectively resist attacks, thus ensuring the security of the gateway. Therefore, the research on the security of the IoT edge devices plays a positive role in reducing the risk of data leakage and the wide application of the IoT system.